A Comparative Study of Student Engagement, Satisfaction, and Academic Success among International and American Students - Korobova, Nadia; Starobin, Soko S. (Journal of International Students, 2015)
This study examines the relationship between student engagement, student satisfaction, and the academic success of international and American students using 2008 National Survey of Student Engagement (NSSE) data. It was found that international students scored slightly higher than American students on enriching educational experiences and supportive campus environment/institutional emphases during their senior year benchmarks. Further, international and American students similarly evaluated their entire educational experience at this institution between good and excellent; however, American students evaluated it slightly higher than international students. Additionally, academic success measured by grades was between B+ and A- for both groups of students; however, international students evaluated it slightly higher than American students. Finally, it was found that the best predictors of satisfaction with the entire experience at this institution and academic success measured by grades were the five benchmarks of effective educational practice.